Spectrophotometric Assay of Dipyrone in Pharmaceutical Preparations Via Oxidative Coupling Reaction with - E.S. Salih; M Al-Sharook (College of Education for Pure Sciences, 2008)
Abstract A simple, rapid and highly sensitive spectrophotometric method has been described for the determination of dipyrone in a bulk and in dosage forms. The method depends on the organic oxidative coupling reaction of dipyrone with m-toluidine in the presence of potassium hexacyanoferrate (III) in aqueous solution to form purple product measured at 530 nm. Beer's law is obeyed in the concentration range 0.4-10.0 g.ml-1 with accuracy (average recovery) of 99.71% and precision (RSD) is less than 2%. The molar absorptivity is 40770 l.mol-1.cm-1 with LOD 0.051 g.ml-1 and LOQ 0.167 g.ml-1. The analytical results agree favourably with official method (iodimetric method) and also with certified values.